Relationship between plant size and ant associates in two Amazonian ant-plants - Vasconcelos, Heraldo L.; Davidson, Diane W. (Biotropica, 2000)
A survey of two Amazonian melastome ant-plants, Maieta guianensis and Tococa bullifera, revealed a significant difference in plant size according to the species of ant inhabiting the plant. Plants with Crematogaster laevis, on average, were smaller than those with Pheidole minutula (in M. guianensis) and those with Azteca sp. (in T. bullifera). There is no evidence that these patterns were due either to the deterministic replacement of C. laevis by another ant species during host-plant ontogeny or to a habitat effect on plant growth rates coupled with colony survival. More likely, the smaller size of C. laevis plants can be explained by its effects on host-plant performance. Plants with C. laevis lost their associated ant colonies more frequently than plants with P. minutula and Azteca sp. Plants that lost their C. laevis either died, or more commonly, were severely defoliated. Defoliated plants, once sprouted, tended to become recolonized, but such recolonizations were not deterministic so as to favor one species over another. Plants with C. laevis showed similar, or only slightly greater, standing levels of herbivory than plants with P. minutula or Azteca sp. This suggests that when C. laevis is present, it confers some degree of protection to its hosts. It was found that early in colony development, queens of C. laevis moved off their host plants to build satellite nests in dead twigs on the ground, a behavior not seen in the other two species and one that possibly renders colonies more vulnerable to mortality from predation, flooding, or nest decay. Comparable δ15N values in C. laevis and P. minutula indicate that the two species are equally dependent on food supplied by the host plant.
Keywords: Ant; Interspecific Interaction; Plant Insect Interaction; Azteca; Crematogaster Laevis; Maieta Guianensis; Pheidole Minutula; Tococa Bullifera